Impact on affected families and society of severe rotavirus infections in Swedish children assessed in a prospective cohort study. Issue 5 (4th May 2018) - Tran, Anh Nhi; Husberg, Magnus; Bennet, Rutger; Brytting, Maria; Carlsson, Per; Eriksson, Margareta; Storsaeter, Jann; Österlin, Barbro; Johansen, Kari
Abstract: Background: Few prospective cohort studies have estimated the overall impact of severe rotavirus gastroenteritis (RVGE) leading to hospitalization on families and society. We assessed human and economic resources needed to care for an affected average child aged <5 years in Sweden. Methods: The study was conducted in Astrid Lindgren Children's Hospital which serves approximately 14% of all Swedish children <5 years of age. All children admitted with acute gastroenteritis in the study period were tested for rotavirus. Health care consumption was collected prospectively and publically available unit costs used to calculate direct costs. Non-medical and indirect costs were collected in interviews with families using a standardized questionnaire during the hospital stay and approximately 14 days post-discharge. Results: 144/206 children (70%) with laboratory-confirmed RVGE were included. The median age was 14 months. The average total cost per hospitalized child was €3894, of which €2169 (56%) was due to direct healthcare-related costs (including Emergency Department visits and in-patient care), €104 (2%) to non-medical direct costs and €1621 (42%) to indirect costs due to productivity loss. Carers of children with severe RVGE were absent from work on average five days per study child: four days during hospitalization of affected child and one day due to gastroenteritis in the carer. Conclusions: Costs for RVGE are dominated by direct costs which are similar to some other countries in Europe, but indirect costs due to productivity loss are also important, and should be considered in decisions to introduce rotavirus vaccines into national vaccination programmes.